Study a New Subclasses of Analytic Bi-Univalent Functions Defined by New Integral Operator - Salih Muhammed, Muhammed; Fadel Abbas, Athra; Razzaq Kadhim, Maryam (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
This paper aims to introduce and examine specific subclass and of analytic and bi-univalent functions defined in the open unit disk , linked to a new integral operator . We examine the upper bounds for the initial Taylor-Maclaurin coefficients also for functions these subclasses.